2023
DOI: 10.1002/ccr3.7000
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar bone exostoses following orthodontic treatment. Diagnostic considerations and clinical management

Abstract: An exostosis is a peripheral overgrowth of bone that is benign and has an undetermined cause. It may be an alveolar surface enlargement that is nodular, flat, or pedunculated. Torus palatinus (TP), torus mandibularis (TM), and alveolar bone exostoses (ABE) are the three anatomical terms for these lesions in the jaws, respectively. 1 Occasionally the same person may develop multiple exostoses. In young, dentate subjects, they may manifest as discrete, isolated bony growths on the facial alveolar bone or, less f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…45 On the other hand, other studies claimed that gender did not influence screw stability. [46][47][48] In the current study, comparing 45 degreewith 90-degree insertion angle showed that more screw stability was found in the 90° group with a statistically significant difference between the two groups (P-value <.01). The present findings seem to be consistent with other research in which greater screw stability was found when the 90-degree insertion angle was performed.…”
Section: Ta B L Esupporting
confidence: 47%
See 1 more Smart Citation
“…45 On the other hand, other studies claimed that gender did not influence screw stability. [46][47][48] In the current study, comparing 45 degreewith 90-degree insertion angle showed that more screw stability was found in the 90° group with a statistically significant difference between the two groups (P-value <.01). The present findings seem to be consistent with other research in which greater screw stability was found when the 90-degree insertion angle was performed.…”
Section: Ta B L Esupporting
confidence: 47%
“…This finding can be explained since males have more bone density than females, which allows better screw stability 45 . On the other hand, other studies claimed that gender did not influence screw stability 46–48 . In the current study, comparing 45 degree‐ with 90‐degree insertion angle showed that more screw stability was found in the 90° group with a statistically significant difference between the two groups ( P ‐value <.01).…”
Section: Discussionmentioning
confidence: 38%